An investigation of elderly problems, a sociological explanation (Case study: Saghez city) - Janmardi, Mahvash (IJRDO - Journal of Social Science and Humanities Research, 2018)
The present research by using the theoretical approach and reference to research findings done in the area of subjects and surveys seeks to describe the aging years, the elderly in different cultures and their problems in the city and to present necessary guidelines for solving elderly problems. On the basis of three theoretical approaches of biology, psychology and sociology such variables as socioeconomic station, marriage status, sustenance, family and relative relations, social relations, physical weaknesses, place of birth, age, positive attitude to the elderly and well-being amenities as independent variables were analyzed at two micro and macro levels on dependent variables of life span, activities , conservatism, isolation, review of past life, social participation, spending the leisure time and effective social relations. Based on data analysis, variables of family and relative relations, well-being amenities, place of birth and marriage status and spending leisure time are significantly related with life span while family and relative relations and physical weaknesses are significantly related with isolation and social relations and socioeconomic station are related with activities, socio economicstation and age. Meantime, attitudes towards the phenomenon of ageingare related with social participation and socioeconomic station is related with activities and physical weaknesses are related with isolation and conservatism. On the other hand, socioeconomic relations are related with social relations and spending leisure times are related with a review of past life. Nevertheless, the variables of socioeconomic station and sustenance are not related with age.